The interview - Association of Social Anthropologists of the UK and the Commonwealth.
1 online resource (288 pages).
Keywords: What are new interview methods and practices in our new 'interview society' and how do they relate to traditional social science research? This volume interrogates the interview as understood, used - and under-used - by anthropologists. It puts the interview itself in the hotseat by exploring the nature of the interview, interview techniques, and illustrative cases of interview use.What is a successful and representative interview? How are interviews best transcribed and integrated into our writing? Is interview knowledge production safe, ethical and representative? And how are interviews used by anthropologists in their ethnographic practice?This important volume leads the reader from an initial scrutiny of the interview to interview techniques and illustrative case studies. It is experimental, innovative, and covers in detail matters such as awkwardness, silence and censorship in interviews that do not feature in general interview textbooks. It will appeal to social scientists engaged in qualitative research methods in general, and anthropology and sociology students using interviews in their research and writing in particular.